Perovskite/Silicon Tandem Solar Cells: Effect of Luminescent Coupling and Bifaciality. Issue 3 (15th January 2021) - Jäger, Klaus; Tillmann, Peter; Katz, Eugene A.; Becker, Christiane
Abstract : The power conversion efficiency of the market‐dominating silicon photovoltaics approaches its theoretical limit. Bifacial solar operation with harvesting additional light impinging on the module back and the perovskite/silicon tandem device architecture are among the most promising approaches for further increasing the energy yield from a limited area. Herein, the energy output of perovskite/silicon tandem solar cells in monofacial and bifacial operation is calculated, for the first time considering luminescent coupling (LC) between two sub‐cells. For energy yield calculations, idealized solar cells are studied at both standard testing as well as realistic weather conditions in combination with a detailed illumination model for periodic solar panel arrays. Typical experimental photoluminescent quantum yield values reveal that more than 50% of excess electron–hole pairs in the perovskite top cell can be utilized by the silicon bottom cell by means of LC. As a result, LC strongly relaxes the constraints on the top‐cell bandgap in monolithic tandem devices. In combination with bifacial operation, the optimum perovskite bandgap shifts from 1.71 eV to the range 1.60–1.65 eV, where already high‐quality perovskite materials exist. The results are very important for developing optimal perovskite materials for tandem solar cells. Abstract : Annual energy yield of perovskite/silicon tandem solar cells under monofacial and bifacial illumination as a function of the perovskite bandgap. The effect of luminescent coupling (LC)–light emitted by the perovskite cell and re‐utilized by the silicon cell–is investigated. LC relaxes the constraints on the top‐cell bandgap, which is important for developing optimal perovskite materials for tandem photovoltaics.